SURGICAL APPROACHES TO CYCLIC PELVIC PAIN IN MAYER–ROKITANSKY–KÜSTER–HAUSER SYNDROME (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Mayer–Rokitansky–Küster–Hauser (MRKH) syndrome is a rare congenital disorder characterized by the absence or underdevelopment of the uterus and the upper two-thirds of the vagina in individuals with a normal female karyotype (46,XX) and fully functioning ovaries. Although primary amenorrhea is often the initial clinical manifestation leading to diagnosis, a subset of patients with MRKH syndrome present with cyclic chronic pelvic pain. This symptom is typically associated with the presence of rudimentary uterine structures containing functional endometrial tissue, which responds to hormonal fluctuations, resulting in hematometra, inflammation, and fibrosis within the pelvic cavity. The management of cyclic chronic pelvic pain in MRKH syndrome presents significant clinical challenges, particularly due to the anatomical variability of the rudimentary structures and the risk of misdiagnosis or delayed treatment. Imaging modalities such as MRI and transabdominal or transrectal ultrasound are critical for the identification of endometrial cavities in non-communicating uterine remnants. Surgical intervention remains the primary therapeutic approach in symptomatic cases. Among the surgical options, endometrial ablation (cauterization) of the rudimentary uterus has emerged as an effective method for eliminating functional endometrium, thereby alleviating pain and reducing the risk of endometriosis and future recurrence. This article provides a comprehensive overview of the etiopathogenesis, clinical presentation, diagnostic workup, and therapeutic strategies for cyclic pelvic pain in MRKH patients, with a special focus on the role of endometrial cauterization. Furthermore, the article underscores the importance of a multidisciplinary approach involving gynecologists, radiologists, surgeons, psychologists, and pain management specialists to ensure timely diagnosis, individualized treatment planning, and holistic patient care. Recognizing and addressing chronic pain in this population not only improves quality of life but also mitigates the psychological burden associated with this complex congenital condition.